Model studies and quantitative evaluation of the reduction of gyttja consolidation settlement by different types of piled raft foundations - Grzegorz Kacprzak; Mateusz Frydrych (Archives of Civil Engineering)
Combined Pile-Raft Foundations (CPRF) are widely employed to mitigate vertical settlement in building and engineering structures. For structures resting on cohesive and organic soils, understanding the time required for complete stabilization of settlement is crucial. The total settlement involves instantaneous settlement (elastic ground deformation), consolidation settlement (water squeezing from pore space), and secondary settlement (structural changes in the ground skeleton, known as secondary consolidation or soil creep). Urban expansion, notably in cities like Warsaw, compels developers to construct in previously overlooked areas, potentially containing organic carbonate sediments like gyttja and chalk. Buildings on such organic soils often settle due to gyttja consolidation during construction and operation. Analyzing long-term settlement, especially of CPRF on reconsolidated organic soils, becomes paramount. Model tests on a laboratory scale offer a cost-effective alternative to large-scale tests, providing quantitative insights into CPRF settlement reduction through piles. This study presents results from model tests conducted on natural organic soils, enabling the prediction of CPRF settlement solely based on gyttja’s geotechnical parameters.